Evaluation of inductively coupled plasma mass spectrometry for determining Ca, Cu, Fe, Mg, Mn, Se and Zn in bovine semen samples using a simple sample dilution method - Aguiar,Giovanna F. M. (2012)
A simple and fast method for the determination of Ca, Cu, Fe, Mg, Mn, Se and Zn in bovine semen by quadrupole inductively coupled plasma spectrometry (q-ICP-MS) is described. Prior to analysis, samples (200 µL) were diluted 1:50 in a solution containing 0.01% v/v Triton® X-100 and 0.5% v/v nitric acid and directly analyzed by ICP-MS. The limits of detection of the method are 0.3, 0.03, 0.2, 0.04, 0.04, 0.03 and 0.03 µg L-1 for 44Ca, 63Cu, 57Fe, 24Mg, 64Zn, 82Se and 55Mn, respectively. For purposes of comparison and method validation, four ordinary bovine semen samples were directly analyzed by ICP-MS and by flame atomic absorption spectrometry (FAAS) or graphite furnace atomic absorption spectrometry (GF AAS), with no statistical difference between the techniques at the 95% level when applying the t-test. Then, the proposed method was applied in the determinations of Ca, Cu, Fe, Mg, Mn, Se and Zn in collected samples of bovine semen from different breeds, which are used in reproduction programs and artificial insemination.